Finite element analysis of plate-screw systems used in medial opening wedge proximal tibial osteotomies. (2015) - Kimsal, Julie; Mercer, Deana; Schenck, Robert; DeCoster, Thomas; Bozorgnia, Shahram; Fitzpatrick, Jennifer; Mlady, Gary; Lerma, Jesus; Khraishi, Tariq
This study investigates, through finite-element analysis, different plate-screw fixation systems used for medial opening proximal tibial osteotomies (locking or non-locking with or without a medial spacer). Sulzer stainless steel non-locking without spacer, Synthes titanium locking without spacer, Smith and Nephew custom titanium locking with a wedge spacer and Arthrex stainless steel non-locking with a wedge spacer fixation systems were modelled and compared. All fixation systems were tested under static loading of 889 N applied evenly over the proximal tibia particular surface. The areas of highest stress experienced in the bone and the plate/screw interface were analysed. Tendency of the osteotomy wedge to close under loading for each fixation system was analysed. The numerical results suggest the titanium locking plate with wedge spacer block outperforms the others by achieving lower stresses (incurred by the fixation system and bone) and loss of correction. Locking screw mechanisms and wedge spacer blocks appear advantageous.